Native nephrectomy in patients with autosomal dominant polycystic kidney disease in kidney transplant program: long-term single-center experience - Navratil, Pavel; Chalupnik, Jiri; Merkl, Tomas; Spacek, Jiri; Matyskova Kubisova, Michaela; Safranek, Roman; Novak, Ivo; Pacovsky, Jaroslav; Navratil, Pavel; Gunka, Igor (International urology and nephrology, 2025)
INTRODUCTION: Autosomal dominant polycystic kidney disease (ADPKD) is a common genetic disorder that frequently leads to end-stage renal disease. In this study, we examine the indications, procedures, and outcomes of native nephrectomy (NN) in ADPKD patients at our transplant center. Drawing on 25 years of clinical practice, we aim to provide insights into the surgical management of ADPKD, focusing on the specific factors influencing NN. MATERIALS AND METHODS: A retrospective study was conducted involving ADPKD patients who underwent KT and NN between 1999 and 2023. Collected data encompassed demographics and surgery parameters, such as duration, hospital stay length, blood loss, and complications. Patients were classified based on the urgency (acute/planned) of the NN and its type (unilateral/bilateral), followed by an analysis of the outcomes per group. RESULTS: Out of 152 patients post-KT for ADPKD, 89 (58.6%) underwent NN. The procedures were predominantly unilateral (71; 64%), with bilateral NN accounting for 40 (36%) cases. NN timing relative to KT was 31 (27.9%) pretransplant, 9 (8.1%) concomitant, 51 (45.9%) posttransplant, and 10 (9%) patients undergoing the sandwich technique. Acute NN were performed in 42 cases, while 69 were planned. Acute NNs were associated with longer surgeries, greater blood loss, and a higher incidence of perioperative complications compared to planned NNs. Specifically, unilateral acute NN had a 23.8% complication rate compared to 2.9% in planned cases; bilateral acute NN showed a 28.6% complication rate versus 4.3% in planned cases. CONCLUSION: This investigation accentuates the significance of planning and selection in NN for ADPKD, factoring in the heightened risk of complications. Acute NN are linked to worse outcomes, including higher rates of complications. The data emphasize the necessity of tailored surgical approaches based on individual patient circumstances.
Keywords: Kidney transplantation; polycystické ledviny autozomálně dominantní; nefrektomie; Retrospective Studies; transplantace ledvin; Time Factors; výsledek terapie; Middle Aged; mužské pohlaví; Adult; ADPKD; Postoperative Complications; ženské pohlaví; Nephrectomy; Kidney Transplantation; Native nephrectomy; retrospektivní studie; Humans; časové faktory; lidé středního věku; Polycystic Kidney, Autosomal Dominant; dospělí; Female; Treatment Outcome; Autosomal dominant polycystic kidney disease; pooperační komplikace; lidé; Male